Biological Relationship of Meloidogyne hapla Populations to Alfalfa Cultivars - Griffin, G D (Journal of nematology, 1995)
Greenhouse and growth chamber studies were established to determine if there are pathological and physiological differences among Meloidogyne hapla populations from California (CA), Nevada (NV), Utah (UT), and Wyoming (WY) on alfalfa cultivars classified as resistant or susceptible to root-knot nematodes. In the greenhouse, plant survival was not consistent with resistance classifications. While all highly resistant Nevada Synthetic germplasm (Nev Syn XX) plants survived inoculation with all nematode populations, two cultivars classified as moderately resistant ('Chief' and 'Kingstar') survived (P </= 0.05) inoculation with M. hapla populations better than did 'Lobo' cultivar, which is classified as resistant. Plant growth of Nev Syn XX was suppressed by only the CA population, whereas growth of the other alfalfa cultivars classified as M. hapla resistant or moderately resistant was suppressed by all nematode populations. Excluding Nev Syn XX, all alfalfa cultivars were severely galled and susceptible to all nematode populations. Except for Nev Syn XX, reproduction did not differ among the nematode populations on alfalfa cultivars. Nev Syn XX was not as favorable a host to CA as were the other cultivars; but, it was a good host (reproductive factor [Rf] = 37). Temperature affected plant resistance; the UT and WY populations were more pathogenic at 15-25 C, and CA was more pathogenic at 30 C. Nev Syn XX was susceptible to all nematode populations, except for CA, at only 30 C, and all other alfalfa cultivars were susceptible to all nematode populations at all temperatures